Effects of Surgical Position on Patients’ Arterial Blood Gases During Percutaneous Nephrolithotomy - Karami, Hossein; Rezaei, Ali Reza; Mazloomfard, Mohammad Mohsen; Javanmard, Babak; Lotfi, Behzad; Haji-Mohammadmehdi-Arbab, Amir (Urology Journal, 2012)
PURPOSE: To compare arterial blood gas analysis of patients who underwent percutaneous nephrolithotomy (PCNL) in flank position under ultrasonography guidance with PCNL in prone and supine positions under fluoroscopic guidance. MATERIALS AND METHODS: In a clinical trial, a total of 90 patients with no upper urinary tract abnormalities were candidate for the PCNL. They were assigned into three groups using pseudorandomization method (30 patients in each group). Patients in group 1 underwent ultrasonography-guided PCNL in flank position. Patients in groups 2 and 3 underwent fluoroscopic-guided PCNL in prone and supine positions, respectively. Arterial blood gas was taken just before and 20 minutes after repositioning. RESULTS: The patients’ mean age was 40.8 ± 6.9, 39.4 ± 10.6, and 37.2 ± 11.1 years in flank, prone, and supine positions, respectively (P = .69). The mean body mass index was 27.8 ± 3.4, 26.7 ± 4.7, and 28.1 ± 5.1 kg/m2 in flank, prone, and supine positions, respectively (P = .21). Arterial oxygen pressure (PaO2) increased significantly in flank (111.7 ± 43.8 to 132.8 ± 58.1 mmHg; P = .01) and prone (118.6 ± 50.2 to 134.6 ± 58.5 mmHg; P < .001) positions and decreased nonsignificantly in supine group (121.7 ± 64.5 to 119.7 ± 60.9 mmHg; P = .23). With surgical positioning, there were no significant changes demonstrated in PaCO2 and serum concentration of HCO3 in the flank, prone, and supine groups. CONCLUSION: We could suggest that flank and prone positions could improve patients’ oxygenation during PCNL procedure.